Postoperative Bleeding and Associated Utilization following Tonsillectomy in Children: A Systematic Review and Meta-analysis. (March 2017) - Francis, David O.; Fonnesbeck, Christopher; Sathe, Nila; McPheeters, Melissa; Krishnaswami, Shanthi; Chinnadurai, Sivakumar
Objective: To assess posttonsillectomy hemorrhage (PTH), associated nonoperative readmissions/revisits, and reoperations in children. Data Sources: MEDLINE, EMBASE, and the Cochrane Library. Review Methods: Two investigators independently screened studies against predetermined criteria and extracted key data. Investigators independently assessed study risk of bias and the strength of the evidence of the body of literature. We calculated unadjusted pooled estimates of PTH frequency and conducted a Bayesian meta-analysis to estimate frequency of primary and secondary PTH and PTH-associated reoperation and revisits/readmissions by partial and total tonsillectomy and surgical approach. Results: In meta-analysis, the frequency of primary and secondary PTH associated with total and partial tonsillectomy was <4% for any technique and with overlapping confidence bounds. Pooled frequencies of PTH were also <5% overall (4.2% for total tonsillectomy, 1.5% for partial tonsillectomy) in comparative studies. Fewer PTH episodes occurred with tonsillectomy for obstructive sleep-disordered breathing than for throat infection. In meta-analysis, frequency of PTH-associated nonoperative revisits/readmission or reoperation ranged from 0.2% to 5.7% for total tonsillectomy and from 0.1% to 3.7% for partial tonsillectomy. At least 4 deaths were reported in case series including 1, 778, 342 children. Conclusions: PTH occurred in roughly 4% of tonsillectomies in studies included in this review. Although studies typically did not report bleeding severity or amount, relatively few episodes of PTH necessitated reoperation for hemostasis. Nonetheless, tonsillectomy is not without risk of harm. Frequency of PTH across techniques was similar; thus, we cannot conclude that a given technique is superior.